2002
DOI: 10.1149/1.1489687
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Lithium Ions in Mixed Organic Electrolyte Solutions by Electrospray Ionization Mass Spectroscopy

Abstract: Solvation of lithium ions in mixed organic electrolyte solutions for secondary lithium batteries was investigated by electrospray ionization mass spectroscopy. The electrolyte solutions were mixed binary solutions of diethyl carbonate ͑DEC͒, dimethyl carbonate ͑DMC͒, ethylene carbonate ͑EC͒, ␥-butyrolactone ͑GBL͒, and propylene carbonate ͑PC͒ containing LiClO 4 . Lithium ions solvated mainly to two solvent molecules. The order of the inclination of the solvent molecules solvating to lithium ions is PC Ͼ EC Լ G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 21 publications
6
59
1
Order By: Relevance
“…Thus, both solvated species reach equilibrium in the solution. In the ESI-MS study, it was reported that Li + (PC) 3 was observed [12][13][14]. However, there is no contradiction between the ESI-MS study and the present work.…”
Section: Single Reflection Atr Spectracontrasting
confidence: 57%
See 1 more Smart Citation
“…Thus, both solvated species reach equilibrium in the solution. In the ESI-MS study, it was reported that Li + (PC) 3 was observed [12][13][14]. However, there is no contradiction between the ESI-MS study and the present work.…”
Section: Single Reflection Atr Spectracontrasting
confidence: 57%
“…On the other hand, it is well known that when lithium ions are solvated using nonaqueous organic solvents [6][7][8][9][10][11][12][13][14], the solvents affect the reduction potential and the subsequent decomposition reactions. When considering rechargeable lithium ion batteries, it is important to understand the behavior of species solvated to lithium ions during the charging and discharging phases.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these systems, the overwhelmingly abundant species detected were the solvation complexes of lithium with the cyclic solvents (EC, PC, or γBL), with coordination numbers between 2 and 3. 173 This selective solvation of lithium ions by highsolvent molecules would exclude the solvents of low-η from the solvation sheath and leave the latter as free, noncoordinating solvent molecules. As a result, the media in which the solvated ions migrate are mainly composed of these free solvent molecules, which impart their low-η to benefit the movement of the solvated ions.…”
Section: Ion Transport Propertiesmentioning
confidence: 99%
“…[30][31][32] To overcome these disadvantages, researchers have introduced the concept of hybrid electrolytes, where an organic solvent is added to the ionic liquid electrolytes so as to increase the room temperature ionic conductivity as well as to get better interfacial behaviour. 15,20,[33][34][35][36] In this work, we have tested hybrid electrolytes composed of 40 wt% ionic liquid in a conventional electrolyte system to understand the role of the ionic liquid in the passivation mechanism of aluminium foil current collector. The proportion of 40 wt% ionic liquid was chosen as a compromise between improved safety and low viscosity for these electrolytes at room temperatures.…”
Section: Introductionmentioning
confidence: 99%